Ab initio prediction of a metallic Bi2C monolayer with high light absorption. (1st April 2022) - Fu, Xi; Cheng, Xiaoli; Liao, Wenhu; Guo, Jiyuan; Li, Liming
Abstract: Two-dimensional materials are attractive for applications in next-generation nanoelectronic devices. In this paper, using particle swarm optimization methodology for crystal structure prediction and first-principles density functional theory, we investigated two-dimensional binary crystals Bim Cn with different chemical compositions. A stable Bi2 C monolayer was predicted with its stability examined by cohesive energy, Born criteria, first-principle MD simulations and phonon spectra, respectively. By including the spin-orbit coupling effect, the Bi2 C monolayer is a metallic two-dimensional material. Using strain engineering method, absorption coefficients of the Bi2 C monolayer can be up to >20% of incident light at the visible light area, and achieve 35% of incident light at the infrared light area when the strain ratio is −4%. These consequences make the Bi2 C monolayer to be an ideal optoelectronics and nanoelectronics material, respectively. Highlights: A metallic Bi2 C monolayer is predicted with its stability examined by cohesive energy, Born criteria, MD simulations and phonon spectra. Absorption coefficients of the monolayer can reach up to >20% for the visible light and to 35% for the infrared light. The Bi2 C monolayer is an ideal optoelectronics and nanoelectronics material.